2017
DOI: 10.1103/physrevfluids.2.014601
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic character of low-order turbulent flow descriptions through the proper orthogonal decomposition

Abstract: Proper orthogonal decomposition (POD) is applied to distinct data sets in order to characterize the propagation of error arising from basis truncation in the description of turbulence. Experimental data from stereo particle image velocimetry measurements in a wind turbine array and direct numerical simulation data from a fully developed channel flow are used to illustrate dependence of the anisotropy tensor invariants as a function of POD modes used in low-order descriptions. In all cases, ensembles of snapsho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 39 publications
(54 reference statements)
1
8
0
Order By: Relevance
“…As Hamilton et al [39,47], we find that the spatial dependence of the local SKE u (y, z) 2 t of the wake flow can already be captured by a few modes (Figure 8), in our case approx. four modes.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…As Hamilton et al [39,47], we find that the spatial dependence of the local SKE u (y, z) 2 t of the wake flow can already be captured by a few modes (Figure 8), in our case approx. four modes.…”
Section: Resultssupporting
confidence: 83%
“…This indicates that most relevant large-scale effects are captured by 6 modes while the small-scale effects are captured by the homogeneous turbulent field, which is moving with the wake structure. Similarly, Hamilton et al [47] found that lower order POD modes are responsible for the anisotropy in the wake while the higher order modes mostly contribute to higher-order and small-scale turbulence. There is however a fundamental difference in our approach since we add the homogeneous field only to the instantaneous wake deficit and not to the ambient field.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Truncating the basis of POD modes before reconstructing velocity snapshots as in Equation results in a filtered description of the turbulence. Low‐rank modes are taken to be the most energetic and anisotropic structures in the flow field; intermediate and high‐rank POD modes account for turbulence kinetic energy that is more homogeneously distributed and more isotropic, detailed in Hamilton et al The point at which the POD basis is truncated is typically determined by choosing a desired level of the TKE according to the eigenvalues, λ .…”
Section: Theorymentioning
confidence: 99%